Introduction - Deborah Hauptmann; Lara Schrijver (Footprint)
Over the past fifteen years most advanced education programmes within Schools of Architecture have been questioning the parameters and requirements of doctoral research both in terms of content and form. This double issue of Footprint was motivated by the question of where the field stands today. Footprint 10|11 presents nine contributions from both recently defended and developing PhD candidates from a variety of institutions. The diversity of their work, as well as the similarities found in the submissions, offers a partial view into research topics currently addressed in PhD programmes within Schools of Architecture.